TEACHING ENGLISH VOCABULARY USING CROSSWORD PUZZLE GAME AT THE SEVENTH GRADE STUDENTS - Yayang Taofik Anwar; Efransyah Efransyah (IKIP Siliwangi, 2018)
Teaching English is one of activity in the classroom. A game can use to improve students’ vocabularies mastery in the process of teaching learning, so students do not get bored while studying English. This research is attempted to verify the effectiveness of the Crossword Puzzle Game in teaching vocabulary at the seventh grade students of SMPN 10 Cimahi. The main objective is to figure out whether the crossword puzzle game is effective to improve the students’ vocabularies or not. The method is used quantitative research and pre-experimental research design conducted in one class. The populations of this research are the seventh grade students. And the sample is one class of the seventh grade students, which is class VII.E that consists of 32 students. The data is collected with the pretest and posttest as an instrument. The data analysis shows the result of mean score of posttest is higher than mean score of the pretest. The result of computation using Wilcoxon based on the table of test statistics, asymptotic significance (2-tailed) = 0.000 which is lower than 0.05. It means the alternative hypothesis is supported. Therefore, teaching English vocabulary using crossword puzzle game is effective to improve the students’ vocabulary. Keywords: Teaching, Vocabulary, Crossword Puzzle Game